Pengaruh Keaktifan Organisasi Terhadap Kefokusan Belajar Mahasiswa Fakultas Tarbiyah dan Keguruan UIN Ar- Raniry - Wirdani, Wirdani; Amanda, Shafa; Irzah, Nurisnah Restu; Triana, Sela Okta; Nelisma, Yuliana; Elviana, Elviana (Journal of Islamic Education, 2025)
The purpose of the study was to determine the effect of organizational activity on the learning focus of students of the Faculty of Tarbiyah and Teacher Training, UIN Ar-Raniry. The quantitative research method is a descriptive approach, with the aim of describing the object of research or research results. The population in this study were all guidance and counseling students and the sample was only 28 guidance and counseling students. The results of the study showed that organizational activity and learning motivation simultaneously had a significant effect on academic achievement. Partially, organizational activity had a significant effect on academic achievement. Partially, learning motivation had a significant effect on academic achievement